2000
DOI: 10.1016/s0896-6273(00)80902-2
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Targeting Signal for Proximal Clustering of the Kv2.1 K+ Channel in Hippocampal Neurons

Abstract: The discrete localization of ion channels is a critical determinant of neuronal excitability. We show here that the dendritic K+ channels Kv2.1 and Kv2.2 were differentially targeted in cultured hippocampal neurons. Kv2.1 was found in high-density clusters on the soma and proximal dendrites, while Kv2.2 was uniformly distributed throughout the soma and dendrites. Chimeras revealed a proximal restriction and clustering domain on the cytoplasmic tail of Kv2.1. Truncations and internal deletions revealed a 26-ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
336
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(363 citation statements)
references
References 50 publications
24
336
0
Order By: Relevance
“…With this approach, we uncovered that Kv2.1 and Kv4.2 channels are sorted into different types of transport vesicles, which display different movement dynamics and distribu-tions. The specific sorting into vesicles was found to be dictated by previously reported peptide targeting motifs present in Kv2.1 (9) and Kv4.2 (10). Quantitative analysis revealed that the differential targeting of Kv2.1 and Kv4.2 post-Golgi transport vesicles is mediated by distinct molecular mechanisms.…”
mentioning
confidence: 76%
“…With this approach, we uncovered that Kv2.1 and Kv4.2 channels are sorted into different types of transport vesicles, which display different movement dynamics and distribu-tions. The specific sorting into vesicles was found to be dictated by previously reported peptide targeting motifs present in Kv2.1 (9) and Kv4.2 (10). Quantitative analysis revealed that the differential targeting of Kv2.1 and Kv4.2 post-Golgi transport vesicles is mediated by distinct molecular mechanisms.…”
mentioning
confidence: 76%
“…Primary hippocampal cultures were prepared as described (19). Cultured neurons were transfected at stage 5, a stage when synapses have been formed and endogenous synaptic receptors have polarized and localized to the synapses.…”
Section: Methodsmentioning
confidence: 99%
“…Contrast and brightness were set so that all pixels were in the linear range. Immunofluorescence staining of neurons was performed as described (19). Immunofluorescent images were captured with IP Labs on a Zeiss Axiophot epiflurescence photomicroscope.…”
Section: Figmentioning
confidence: 99%
“…One of the hallmarks of Kv2.1 expression in mammalian neurons is specific targeting to large, high-density cell surface clusters restricted to the soma and proximal dendrites (8,12,13). Interestingly, not only is channel voltage dependence altered by the aforementioned stimuli, but also channel localization.…”
mentioning
confidence: 99%